The blossom and the firefly - Smith, Sherri L. (New York : G. P. Putnam's Sons, 2020)
Told in two voices, seventeen-year-old kamikaze pilot Taro and fifteen-year-old war worker Hana meet in 1945 Japan, he with no future and she, haunted by the past. Includes historical notes and glossary.
Keywords: World War, 1939-1945 -- Japan -- Fiction; World War, 1939-1945 -- Japan -- Juvenile fiction; Kamikaze pilots -- Fiction; Musicians -- Fiction; Family life -- Japan -- Fiction